2013
DOI: 10.5194/hess-17-2435-2013
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater–surface water interactions, vegetation dependencies and implications for water resources management in the semi-arid Hailiutu River catchment, China – a synthesis

Abstract: Abstract. During the last decades, large-scale land use changes took place in the Hailiutu River catchment, a semiarid area in northwest China. These changes had significant impacts on the water resources in the area. Insights into groundwater and surface water interactions and vegetationwater dependencies help to understand these impacts and formulate sustainable water resources management policies. In this study, groundwater and surface water interactions were identified using the baseflow index at the catch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 38 publications
3
39
0
Order By: Relevance
“…Using the HYSEP automated hydrograph separation method (Sloto and Crouse, 1996) on the daily streamflow data, such "observed" groundwater discharge data were obtained. For C1, these data were partly reported in Zhou et al (2013).…”
Section: Model Calibrationmentioning
confidence: 99%
“…Using the HYSEP automated hydrograph separation method (Sloto and Crouse, 1996) on the daily streamflow data, such "observed" groundwater discharge data were obtained. For C1, these data were partly reported in Zhou et al (2013).…”
Section: Model Calibrationmentioning
confidence: 99%
“…Groundwater dependency of ecosystems can also be quantified using a water budget approach [12,84,85]. If the total amount of water that is being used by terrestrial vegetation in a given site for a specific time period can be demonstrated to be considerably larger than the total precipitation for this site, and there is no significant lateral flow, it can be concluded that this ecosystem depends to a certain degree on groundwater [12].…”
Section: Ground-based Methods Useful In Identifying Groundwater Depenmentioning
confidence: 99%
“…Several authors have documented the ecosystem response to landforms and how the composition and structure of vegetation is determined by geomorphic events [85,129]. Landforms (usually characterized by topography and geology) deeply influence spatial variations in ecological variables such as water availability and exposure to radiant solar energy.…”
Section: Integration Of Remotely Sensed Data With Ground-based Observmentioning
confidence: 99%
“…The Hailiutu River basin, which belongs to the middle Yellow River basin, is a typical sandy grass shoal watershed in the Erdos plateau in northwest China. This basin has undergone climate variability and land use change in recent decades [32]. Studies showed that in the central-south Yellow River basin the intensity of precipitation extremes increased between the years 1986 and 2011, and may have resulted in increased surface runoff [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also showed that streamflow change is more sensitive to precipitation than temperature in the Yellow River basin, especially in the middle section [36,37]. Because of the implementation of the desert greening policy, the land use of study area has changed, i.e., increasing the area of shrub and grass land and decreasing the area of sand land [32]. The increased shrub and grass land could result in decreased baseflow and increased surface runoff and evapotranspiration [6,15].…”
Section: Introductionmentioning
confidence: 99%